Measurement of the W boson helicity fractions in the decays of top quark pairs to lepton plus jets final states produced in pp collisions at root s=8 TeV - Khachatryan, V. (2016)
The W boson helicity fractions from top quark decays in t (t) over bar events are measured using data from proton-proton collisions at a centre-of-mass energy of 8 TeV. The data were collected in 2012 with the CMS detector at the LHC, corresponding to an integrated luminosity of 19.8 fb(-1). Events are reconstructed with either one muon or one electron, along with four jets in the final state, with two of the jets being identified as originating from b quarks. The measured helicity fractions from both channels are combined, yielding F-0 = 0.681 +/- 0.012 (stat) +/- 0.023 (syst), F-L = 0.323 +/- 0.008 (stat) +/- 0.014 (syst), and F-R = -0.004 +/- 0.005 (stat) +/- 0.014 (syst) for the longitudinal, left-, and right-handed components of the helicity, respectively. These measurements of the W boson helicity fractions are the most accurate to date and they agree with the predictions from the standard model. (C) 2016 The Author. Published by Elsevier B.V.